Analysis of Integrated Civics Learning in Character Education Literacy on SD Negeri Taipeleleng, Gowa Regency - Sukmawati Sukmawati; Idawati Idawati; Nursalam Nursalam (Universitas Muhammadiyah Enrekang, 2022)
This research is a qualitative descriptive study that aims to 1) describe the integrated Civics learning of character education literacy; 2) reviewing the implementation of integrated Civics learning literacy in character education; 3) know the evaluation. Civics learning is integrated with character education literacy. Data collection techniques used interview, observation, and documentation techniques. Data analysis was carried out through a deductive method consisting of data collection and reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be said that 1) the integrated Civics learning plan for character education literacy in grade IV SD Negeri Taipaleleng includes: a) The teacher conducts a basic analysis and the learning materials to be taught, b) The teacher finds values ​​in basic competencies and subject matter that can be taught, c) the teacher determines the priority values ​​to be taught in one lesson or one basic competency, d) chooses the learning method and model, e) describes the learning steps; (2) Implementation of integrated Civics learning literacy character education in grade IV SD Negeri Taipaleleng carries out core activities including; (1) practice activities, (2) reading activities, (3) observing activities, (4) activity activities; and (3) Evaluation of integrated Civics learning character literacy in grade IV SD Negeri Taipaleleng includes: a) developing assessment instruments based on competency analysis, b) carrying out authentic assessments, c) processing research results objectively, d) reporting results through effective communication to parents (guardians) and teachers in the next, e) the results of the assessment.